The Aggravation of the Situation in Afghanistan: New Threats to Peace and the Ways of their Prevention - S. M. Adilkhodjaeva (Сравнительная политика)
Afghanistan is a long-suffering country in which there is no peace and stability for several decades now. At present, the situation in Afghanistan is uncertain and unpredictable. In this country, there is a danger of escalation of terrorism, religious extremism and the spread of drugs. The article is devoted to the analysis of political, social, economic and humanitarian situation in Afghanistan. It also provides an analysis of the prevention of new threats that have arisen in this country.